Integrated multi-platform metabolomics reveals fatty acid-mediated inflammatory signatures in pretibial myxedema - Cai, Jiayi; Zhang, Li; Zheng, Jie; Pan, Meng; Li, Xia; Zhao, Xiaoqing; Wang, Shuoting; Shang, Zirou; Cao, Han; Chen, Xiaoying (Frontiers in Endocrinology, 2026)
ContextPretibial myxedema (PTM) is a refractory autoimmune dermopathy associated with Graves’ disease. Although metabolic dysregulation has been recognized in thyroid-associated disorders, the metabolic profile and its functional role in PTM remain unclear.ObjectiveTo characterize the metabolic landscape of PTM lesions and explore the contribution of fatty acids to fibroblast dysfunction and inflammation.MethodsWe performed untargeted metabolomic profiling of PTM skin lesions and healthy controls using LC-MS and GC-MS, integrated with spatial metabolomics to localize metabolic changes. Functional assays were conducted by stimulating human foreskin fibroblasts (HFFs) with palmitic acid (PA) and oleic acid (OA), followed by RNA sequencing, cytokine assays, and immunohistochemistry.ResultsPTM lesions exhibited substantial metabolic dysregulation, including accumulation of fatty acids and elevated tricarboxylic acid cycle intermediates. Spatial metabolomics confirmed pronounced lipid deposition in the dermis, the primary site of PTM pathology. RNA-seq of fibroblasts stimulated with PA and OA revealed enrichment of inflammatory pathways, including IL-17 and NF-κB signaling, and marked upregulation of IL-8 (CXCL8). Fatty acid stimulation induced robust IL-8 secretion, consistent with increased IL-8 expression in PTM lesions. Moreover, PA promoted α-SMA expression in fibroblasts, suggesting induction of myofibroblast differentiation.ConclusionsOur findings demonstrate that dermal fatty acid accumulation in PTM may contribute to fibroblast-mediated inflammation and fibrosis. This study provides novel insights into the metabolic-immunologic interface underlying PTM pathogenesis.